A Survey of Contruction of Buddhist Monastery Concerning Śayanāsanavastu and Senāsanakkhandhakapāḷi (International Journal of Food and Nutritional Sciences, 2023)
Having attained enlightenment, the Buddha went everywhere to prograde his dharma; his teachings attracted many people who wanted to enter into religious life. As soon as the Order of the monks formed, they lived here and there as wanders and did not have any permanent place because the Buddha did not allow them to reside in a location for so long. Therefore, at the beginning of the saṅgha ’s life, the monks lived only in temporary locations such as in the forest, under a tree, on a hillside, in a narrow valley, in a mountain, in a cave, in a cemetery, in a forest glade, on an open plain, on a heap of straw, and so on. They went to those places in the evening, and left those places in the morning. As soon as the Buddha took rain retreat, they were allowed to live in a place for three or four months. Having completed the rain retreat, they had to approach another place to preach Dhamma and do missionary work.